Pediatric Liver Abscess: Trends in the Incidence, Etiology, and Outcomes Based on 20-Years of Experience at a Tertiary Center - Yeh, Pai-Jui; Chen, Chien-Chang; Lai, Ming-Wei; Yeh, Hung-Yu; Chao, Hsun-Chin (Frontiers in Pediatrics, 2020)
Background Liver abscess is an important but relatively rare disease in children. This study investigated the clinical characteristics of eligible patients at a referral tertiary center over the past two decades. Method A 20-year retrospective study (January 2000–December 2019) enrolled 38 children diagnosed with liver abscess. Demographic data; clinical features; laboratory, imaging, and microbiological findings; management strategy; and outcomes were reviewed from the patients’ medical records. Results Thirty-eight cases of pyogenic liver abscess were identified without a culture-proven amebic or fungal abscess. The mean age of diagnosis was 9.6 ± 6.2 years, and the male-to-female ratio was 1.92: 1. Hemato-oncological (28.9%) and predisposing hepatobiliary diseases (23.7%) were the two most common predisposing factors. Fever (94.7%) was the most common presentation followed by right upper quadrant abdominal pain (42.1%) and pleural effusion (34.2%). Among the laboratory parameters, leukocytosis was common (70.3%), and all patients had elevated serum C-reactive protein levels. Increased serum levels of alanine aminotransferase, aspartate aminotransferase, direct bilirubin, and total bilirubin were found in 40.5%, 48.6%, 23.1%, and 42.9% of the cases, respectively. The most common pathogen in blood and pus cultures was Klebsiella pneumoniae. The mean durations of intravenous antibiotic and total antibiotic use were 29.0 ± 15.7 days and 45.1 ± 22.1 days, respectively. Twelve patients (31.6%) were treated with antibiotics alone, while percutaneous needle aspiration, percutaneous pigtail drainage, and surgical intervention were performed in 12 (31.6%), 10 (26.3%), and 5 (13.2%) patients, respectively. No mortality was documented in this series. Conclusion The present study reflects a relatively declining incidence of liver abscess compared with prior studies in Taiwan. K. pneumoniae remains the most prevalent pathogen in both blood and abscess cultures in Taiwan. Proper antimicrobial therapy with timely drainage generally yielded an adequate treatment response without any mortality.